Peningkatan Keaktifan Siswa Menggunakan Model Pembelajaran Student Teams Achievement Division - Ajeng Arina Habiibillaah; Elia Ling Ling Melati (Lembaga Bale Literasi, 2023)
This research is a classroom action research that aims to increase student activity through the application of the Student Teams Achievement Division learning model. This research was conducted in class VIII G of SMP Negeri 2 Tengaran in the even semester of the 2022/2023 school year with a total of 34 students. This research was conducted in two cycles. Data collection was carried out using observation and learning achievement tests. The data collected was analyzed using descriptive statistical analysis, where an indicator of the success of this study was an increase in the average value of mastery of science process skills during learning in each cycle. The results showed that in cycle I, an average score of 63 was obtained for 3 students with active criteria, and 31 students got an average score of 57 with moderately active criteria. Cycle II experienced an increase with an activeness score of 83 for 23 students with very active criteria, and as many as 11 students scored 79.5 with active criteria. Thus it can be concluded that the use of the Student Teams Achievement Division (STAD) learning model can increase student activity which has an impact on increasing student learning outcomes